The green vessel schedule design problem: consideration of emissions constraints - Dulebenets, M. A.; Golias, Mihalis; Mishra, Sabyasachee (My University, 2015)
The fluctuating demand of international seaborne trade, overcapacity, and increasing attention to environmental issues force liner shipping companies to improve efficiency of their operations, while complying with the established emissions limitations. This paper proposes a mathematical model for the green vessel scheduling problem, imposing constraints on emissions produced by a vessel at each voyage leg of the liner shipping route. The original mixed integer non-linear mathematical model is linearized and solved efficiently using CPLEX. Numerical experiments are conducted to demonstrate changes in the vessel schedule that a liner shipping company has to make for a given shipping route, when emissions constraints are imposed.
Keywords: Marine transportation; Green vessel scheduling; Energy efficiency; Bunker consumption; Emissions